L'origine de la primauté du privilège d'une banque sur les droits d'un vendeur impayé - Patenaude, Micheline (Les Cahiers de droit, 1981)
In this article, the author studies the reasons that led the legislator to amend, in 1861, a law adopted in 1859 in order to specify that the claim of the holder of a bill of lading or of a warehouse receitpt has priority over the claim of any unpaid vendor. The study is particularly relevant due to the fact that section 179 of the actual Bank Act is directly derivated from the 1861 amendment without any significant modification. The study of the rights held by the pledger and the unpaid vendor at the time when the legislator adopted the above mentioned amendmend leads the author to conclusions as to the reasons that made this amendment necessary, as well as to the significance of section 179 in the Bank Act.